A devil's chaplain : reflections on hope, lies, science, and love - Dawkins, Richard, 1941- (Boston : Houghton Mifflin Co., 2003)
Presents a collection of essays that explore such topics as religion, mysticism, modern educational methods, pseudoscience, Africa, and late colleagues Douglas Adams and Stephen Jay Gould
1 Science and Sensibility 5 -- 2 Light Will Be Thrown 61 -- 3 The Infected Mind 117 -- 4 They Told Me, Heraclitus 163 -- 5 Even the Ranks of Tuscany 187 -- 6 There is All Africa and her Prodigies in Us 223 -- 7 A Prayer for My Daughter 241
Includes bibliographical references and index
Keywords: Evolution (Biology); Science -- Philosophy; Religion and science; Bioethics; Science; Biological Evolution; Bioethics; Genetics; Religion and Science; Science; Bioethical Issues; Collected Work; Popular Work; Popular works